Respuesta :
Subsitution method.
Y=3x - 11
Y= -3x - 2
-3x - 2 = 3x - 11
+3x +3x
-2 = 6x - 11
+11 +11
6x = 9
x = 1.5
Y=3(1.5) - 11
y = 4.5 - 11
y = -6.5
Now we have our points.
Answer: x = 1.5 and y = -6.5
Y=3x - 11
Y= -3x - 2
-3x - 2 = 3x - 11
+3x +3x
-2 = 6x - 11
+11 +11
6x = 9
x = 1.5
Y=3(1.5) - 11
y = 4.5 - 11
y = -6.5
Now we have our points.
Answer: x = 1.5 and y = -6.5
Well, you do Equality method.
3x-11 = -3x-2
add 3x on both sides
6x-11 = -2
add 11 on both sides
6x = 9
divide 6 on both sides
x = 3/2
As you found the x value, you now need to find the y value by plugging in the x value in one of the above equations and solve for y.
y = 3x-11
y = 3(3/2) -11
y = 9/2 -11
y = -13/2
So, the answer is (3/2,-13/2) or (1.5,-6.5)
HOPE THIS HELPS!!!
3x-11 = -3x-2
add 3x on both sides
6x-11 = -2
add 11 on both sides
6x = 9
divide 6 on both sides
x = 3/2
As you found the x value, you now need to find the y value by plugging in the x value in one of the above equations and solve for y.
y = 3x-11
y = 3(3/2) -11
y = 9/2 -11
y = -13/2
So, the answer is (3/2,-13/2) or (1.5,-6.5)
HOPE THIS HELPS!!!